(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The evaluation of the antecedents of users’ continuous usage intention has become essential for the success of ride hailing services. This study analysed the antecedent role of customers’ perceptions and satisfaction with continuous usage intention of ride hailing services in Kerala, India. The model used in this study conceptualizes customers perceptions as a composite variable comprising four dimensions (perceived usefulness, perceived ease of use, perceived value and satisfaction) prescribed by the Technology Acceptance Model (TAM). It employed a descriptive, correlational survey approach in which the responses of 216 registered users of ride hailing were analysed using descriptive inferential statistics. Linear regression analysis indicated that the model provided a statistically significant explanation for the variation in users’ continuous usage intentions. The study also found empirical support for customers’ perceptions (perceived usefulness, perceived ease of use, perceived value and satisfaction) as antecedents of continuous usage intention with ride hailing services.